The walnut (Juglans regia) genome sequence reveals diversity in genes coding for the biosynthesis of non‐structural polyphenols. (18th July 2016) - Martínez‐García, Pedro J.; Crepeau, Marc W.; Puiu, Daniela; Gonzalez‐Ibeas, Daniel; Whalen, Jeanne; Stevens, Kristian A.; Paul, Robin; Butterfield, Timothy S.; Britton, Monica T.; Reagan, Russell L.; Chakraborty, Sandeep; Walawage, Sriema L.; et al.
Summary: The Persian walnut ( Juglans regia L.), a diploid species native to the mountainous regions of Central Asia, is the major walnut species cultivated for nut production and is one of the most widespread tree nut species in the world. The high nutritional value of J. regia nuts is associated with a rich array of polyphenolic compounds, whose complete biosynthetic pathways are still unknown. A J. regia genome sequence was obtained from the cultivar 'Chandler' to discover target genes and additional unknown genes. The 667‐Mbp genome was assembled using two different methods (SOAPdenovo2 and MaSuRCA), with an N50 scaffold size of 464 955 bp (based on a genome size of 606 Mbp), 221 640 contigs and a GC content of 37%. Annotation with MAKER‐P and other genomic resources yielded 32 498 gene models. Previous studies in walnut relying on tissue‐specific methods have only identified a single polyphenol oxidase (PPO) gene ( JrPPO1 ). Enabled by the J. regia genome sequence, a second homolog of PPO ( JrPPO2 ) was discovered. In addition, about 130 genes in the large gallate 1‐β‐glucosyltransferase (GGT) superfamily were detected. Specifically, two genes, JrGGT1 and JrGGT2, were significantly homologous to the GGT from Quercus robur ( QrGGT ), which is involved in the synthesis of 1‐ O ‐galloyl‐β‐d ‐glucose, a precursor for the synthesis of hydrolysable tannins. The reference genome for J. regia provides meaningful insight into the complex pathways required for the synthesis of polyphenols. The walnut genome sequence provides important tools and methods to accelerate breeding and to facilitate the genetic dissection of complex traits. Significance Statement: In walnut, nut and wood quality are highly influenced by polyphenolic diversity, but the biosynthetic pathways for polyphenols are poorly characterized. Here we describe a high‐quality draft genome sequence of the Persian walnut, Juglans regia, which will accelerate breeding and facilitate the genetic dissection of complex traits.